Pengaruh Sterilisasi Ultraviolet-C Terhadap Perubahan Dimensi Hasil Cetak Alginat - William Wijaya; Nova Adrian (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Impression material is a material that is used to negatively replicate a patient's tooth structure and periodontal, and it is preferable to sterilize the negative model first before the casting process to avoid cross-contamination between the dentist and the patient. Then casts are made from the impression using type III gypsum, producing diagnostic cast or working cast. Ultraviolet-C (UV-C) sterilization was introduced as the lastest sterilization technology from UV rays with an effectiveness rate of 99.9% in lysing germs, viruses, and fungi. The wavelength of UV-C light itself is also the smallest at 200-270 nm compared to UV-A 320-400nm and UV-B 270-320nm. Objective: To determine the effect of UV-C sterilization on the changes in dimension of alginate impressions. Methods: The type of this research was experimental laboratory research. The samples were taken from the maxillary model which were divided into 2 groups, namely (A) the treatment group where cast was irradiated with UV-C and (B) the control group where casts were sprayed with disinfectant. Samples of the treatment and control groups were both sterilized first before casted. For the treatment group, casts were put in a UV-C box for 10 minutes. For the control group, casts were sprayed with disinfectant, then covered with a moistened tissue and put into a plastic seal. Result: UV-C sterilization did not show significant changes toward dimensional changes of alginate impressions. Conclusion: UV-C sterilization can be used to sterilize alginate impression materials because it does not cause significant dimensional changes of the impression